Augmented Reality-based Media on Molecular Hybridization Concepts Learning - Irwansyah, Ferli Septi; Asyiah, Efa Nur; Farida, Ida (Universitas Islam Negeri Raden Intan Lampung, 2019)
Students' problems in understanding of the hybridization process need to be overcome by using interactive media. Therefore, this study aimed to analyze the results of the validation test and the feasibility test of learning media based on Augmented Reality (AR) on the concept of hybridization. The research method used was the Design-based Research (DBR) method based on technology that supports the learning process within two stages, namely the analysis stage and the design and development stage. Data collecting instruments used were a validation test questionnaire and a limited trial sheet. The media was validated by 3 expert lecturers and 10 respondents of Chemical Education Department students at UIN Sunan Gunung Djati Bandung, Indonesia. Overall validation test results obtained an average value of robserved of 0.88. The validation test obtained a value above 0.30, which showed that the learning media was valid and can be used for the limited trial. The limited trial obtained an average value of 88.59 % within a feasible category. This research concluded that AR learning media on the concept of hybridization is appropriate to be used as teaching material in the learning.